Acneiform eruption during peficitinib treatment. Issue 4 (1st February 2022) - Hara, Reiko; Sawada, Yu; Nakamura, Motonobu
Abstract : Drug eruption is one of the triggers to cause allergic cutaneous immune reactions to medications. On the contrary, unusual skin clinical manifestation due to medications sometimes is observed by novel medications, which help to get a better understanding of the factor‐mediated skin physiological function. Herein, we report a case of acneiform eruption following a JAK inhibitor, peficitinib.